A case of trust‐building in the supply chain: Emerging economies perspective. (19th January 2022) - Manfredi, Emilia; Capik, Paweł
Abstract: The paper explores the process of trust‐building between SMEs' supply chain partners in turbulent times in emerging economies. It focuses on the role of environmental information exchange in strengthening relationships and improving responsiveness to overcome uncertainty while understanding and adapting to the changing environmental realities. A case study strategy of an SME in Argentina was conducted to obtain insights regarding the experiences, perceptions and opinions about how achieving trust acts as an instrument of partners' support during an uncertain time. A series of semi‐structured interviews were conducted in Argentina and China to collect empirical data. Data were analyzed to understand partners' mutual support and the emergence of trust. The importance of supply chain partnership is that partners go to the market together, meaning that there are more opportunities to benefit from for each partner. The results demonstrate that it is incorrect to assume that an SME can prosper alone in an unknown landscape. However, because of their responsiveness and experience in operating in a turbulent working environment, decision‐makers rapidly develop skills to adapt to uncertainty. Information sharing is at the core of establishing successful long‐term relationships, overcoming uncertainties while transforming them into opportunities.